Pemberdayaan Pelaku UMKM di Kecamatan Jeumpa melalui Pelatihan Strategi Pemasaran Digital Berbasis Media Sosial untuk Peningkatan Penjualan - Mirza; Dedi Saputra; Syah Iskandar; Zulkifli; Mufti Imam (Jurnal Pengabdian Pemersatu Bangsa, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Jeumpa District continue to face challenges in utilizing social media as an effective marketing tool, limiting their market reach and sales performance. This community service program aimed to enhance the knowledge and practical skills of MSME owners in implementing social media-based digital marketing strategies. The program adopted a participatory approach consisting of needs assessment, training sessions, hands-on practice, implementation assistance, and monitoring and evaluation. Participants received training on digital marketing fundamentals, the optimization of Facebook, Instagram, WhatsApp Business, and TikTok, promotional content creation, and business account management. The results demonstrated significant improvements in participants' understanding of digital marketing concepts, their ability to create promotional content, and their competence in utilizing social media for business promotion. The high level of participant engagement and successful implementation during practical sessions indicate that the program effectively strengthened the digital marketing capabilities of MSME owners. This initiative is expected to expand market access, improve product competitiveness, increase sales, and support the long-term sustainability of MSMEs in Jeumpa District.